Lectotype, epitype and amendment of Gastrodia angusta (Orchidaceae) - Li, Jian-Wu; Huang, Lu-Qi; Li, Guo-Wu; Pan, Bo; Yin, Jian-Tao; Jin, Xiao-Hua (Phytotaxa, 2018)
Gastrodia angusta S. Chow et S. C. Chen was established in 1983 from Shiping County, Yunnan Province, China. However, the specimens cited were erroneous: 3 type and 1 isotype were apparently collected on two different days and in different places. Moreover, the description omitted some key characters, including outer surface of sepals lobes with mid-vine convex and with 3–5 dens, margins sometimes irregular erose, lip triangular-oblong, epichile margins undulate and irregular erose, apex rounded and sometime irregular erose, disc with a longitudinal yellow, rugose, 2 mm wide belt, margins of mesochile retrousse and folded, forming two upright, semi-orbicular lamella on hypochile, lamellae inside densely with orange-yellow powder particles (pseudo-pollen). We have therefore designated a lectotype and epitype, and provide a revised description.